The Influence Of Mother’s Perception and Attitude Toward Fish Purchasing Behavior in Pekalongan Families - Safitri, Ima Audina; Muflikhati, Istiqlaliyah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2018)
Purchase behavior is influenced by several factors such as perception and attitude. This study aims to analyze the influence of perceptions and attitudes on fish purchasing behavior in rural and urban areas. This research use cross sectional study design. This research was conducted in Pekalongan. Kandang Panjang Village, Pekalongan City as urban area and Duwet Village, Pekalongan Regency as rural area. The sample in this study was 100 mothers. Data were analyzed using descriptive test, different test Independent sample T-test, Pearson correlation test, and multiple linear regression test. Perception and mother’s attitude in urban were higher than in rural. Beside that, there were differences on fish expenditure, expenditure of fish in urban was higher than in rural. Regression test showed perception, location, and maternal age have a significant effect on fish purchasing behavior.